Manajemen Asuhan Kebidanan Berkelanjutan (Continuity of Care) pada Ibu Hamil, Bersalin, Nifas, dan KB: Studi Kasus di PMB Siti Nur Azizah Sidoarjo - Annisa Alfi Amalia; Putri Ancila Citra Prasetya (PPNI UNIMMAN, 2025)
Continuity of Care (CoC) is a midwifery care model that provides continuous care from pregnancy, childbirth, the postpartum period, and newborn care to family planning services. This approach aims to improve the quality of care, enable early detection of complications, and enhance maternal and neonatal health outcomes. This study aimed to describe the implementation of Continuity of Care midwifery services for Mrs. D, aged 25 years, at PMB Siti Nur Azizah, Wonoayu, Sidoarjo, East Java.This study employed a descriptive method with a case study approach. The subject was Mrs. D, a primigravida woman who received midwifery care from the first trimester of pregnancy through the postpartum period, newborn care, and family planning services. Data were collected through interviews, observation, physical examinations, and medical record review.The results showed that throughout pregnancy, both maternal and fetal conditions remained within physiological limits with routine monitoring and adequate health education. Labor occurred spontaneously and normally with the application of respectful maternity care and interventions based on clinical indications. The postpartum period progressed normally with good uterine involution and adequate breast milk production. The newborn demonstrated optimal physiological adaptation and received essential neonatal care. In the family planning phase, Mrs. D chose a three-month injectable contraceptive, which was appropriate for her breastfeeding condition and pregnancy spacing needs.